Cytogenetic studies in three species of Lutjanus (Perciformes: Lutjanidae: Lutjaninae) from the Isla Margarita, Venezuela - Nirchio, Mauro; Rondón, Rodolfo; Oliveira, Claudio [UNESP]; Ferreira, Irani A. [UNESP]; Martins, Cesar [UNESP]; Pérez, Julio; Sola, Luciana; Rossi, Anna Rita (Sociedade Brasileira de Ictiologia, 2008)
No presente estudo três espécies de Lutjaninae, Lutjanus analis, L. griseus e L. synagris foram analisadas através da coloração convencional com Giemsa, banda C e coloração com nitrato de prata para identificar as Regiões Organizadoras de Nucléolo (NORs) ativas. Hibridação fluorescente in situ (FISH) foi também aplicada para estabelecimento do número e localização dos agrupamentos de genes ribossômicos (18S e 5S rRNA). A contagem de células metafásicas revelou um número diplóide modal de 48 cromossomos acrocêntricos em L. analis e L. griseus. Dois citótipos foram observados em L. synagris: citótipo I com 2n=48 cromossomos acrocêntricos, encontrado em 19 espécimes, e citótipo II com 46 cromossomos acrocêntricos e um grande metacêntrico, encontrado em dois espécimes. O grande metacêntrico, que possivelmente se originou por um rearranjo Robertsoniano, não está relacionado com o sexo. Nas três espécies a heterocromatina constitutiva está localizada nas regiões centroméricas de todos os cromossomos. NORs foram detectadas no braço curto de um único par cromossômico, número 24 em L. analis e número 6 em ambos os citótipos de L. synagris. em L. griseus, um polimorfismo de número de NORs foi observado, após coloração com prata e por FISH, as fêmeas apresentaram um máximo de três NORs e os machos um máximo de seis NORs. em todas as espécies os genes ribossômicos 5S foram encontrados em um único par cromossômico. Os dados obtidos, somados aos demais previamente publicados para cinco outras espécies de Lutjanidae, mostram que na família há uma homogeneidade cromossômica, porém também são encontrados cariótipos derivados, originados por rearranjos Robertsonianos, assim como pela ocorrência de sítios múltiplos e variados de NORs.

In the present study, three species of Lutjaninae, Lutjanus analis, L. griseus and L. synagris, were analyzed by conventional Giemsa staining, C-banding and silver staining, to reveal active Nucleolus Organizer Regions (NORs). Fluorescent in situ hybridization (FISH) was also applied to establish the number and location of the ribosomal gene clusters (18S and 5S rRNA genes). Counts of diploid metaphasic cells revealed a diploid modal chromosome complement composed of 48 acrocentric chromosomes in both L. analis and L. griseus. Two cytotypes were observed in L. synagris: cytotype I, with 2n=48 acrocentric chromosomes, found in 19 specimens, and cytotype II, with 46 acrocentric chromosomes and one large metacentric, found in two specimens. The large metacentric, which possibly originated from a Robertsonian rearrangement, was not found to be sex-related. In the three species, constitutive heterochromatin is located in the centromeres of all chromosomes. NORs were detected on the short arms of a single chromosome pair, number 24 in L. analis and number 6 in both cytotypes of L. synagris. In L. griseus, a polymorphism of the NORs number was detected, by both Ag-staining and FISH, as females show a maximum of three NORs, and males a maximum of six NORs. In all species, minor ribosomal genes were found located on a single chromosome pair. The obtained data, along with those previously reported for other five Lutjanidae species, show that a general chromosome homogeneity occurs within the family, but that derived karyotypes based on Robertsonian rearrangements as well as multiple and variable NORs sites can also be found.
Keywords: Karyotype; Ribosomal genes; NOR polymorphism; C-banding; Robertsonian rearrangement